Stability of a Three-Species Cooperative System with Time Delays and Stochastic Perturbations - Jinxing Zhao; Yuanfu Shao (Discrete Dynamics in Nature and Society)
Considering the impacts of time delays and different kinds of stochastic perturbations, we propose two three-species delayed cooperative systems with stochastic perturbations in this paper. We establish the sufficient criteria of the asymptotical stability and stability in probability by constructing a neutral stochastic differential equation and some suitable functionals. The impacts of time delays and stochastic perturbations to the system dynamics are revealed by some numerical simulations at the end.